Effect of Non-Ionizing Electromagnetic Fields of Anthropic Origin on Male Fertility - Bernabò, Nicola; Ciccarelli, Rosa; Mattioli, Mauro; Barboni, Barbara (Current Chemical Biology, 2016)
This review is aimed to summarize the literature concerning the effect of the exposure to non-ionizing electromagnetic fields (EMFs) of human origin on male reproduction. In particular, we addressed our attention in examining the papers concerning static magnetic fields (SMFs), extremely-low frequency electromagnetic fields (ELF-EMFs), microwaves (MW) and radio frequencies (RF). These EMFs are produced by the technological activity, during medical imaging examinations, in transport and use of electricity, and by telecommunication devices. Consequently, it is virtually impossible to avoid their presence in houses, schools, hospitals, as well as in public places or in workplaces. Recently, ELFEMFs and RF have been classified as “possibly carcinogenic to humans” by the International Agency for Research on Cancer and they have attracted the attention of public and of scientists, because of the concerns about their possible negative effect on human and animal health. In this context, it is of great interest to assess their effect on male reproductive health. Unfortunately, the epidemiological studies carried out until now failed to give a clear evidence of the risk associated with the EMFs exposure for several reasons: it is impossible to define a “typical” exposure profile, the level of risk has the same order of magnitude of the background, and therefore more extensive studies are required. Animal and cellular model also give inconclusive and contradictory results likely due to the difficulty in standardizing the experimental models and due to the exposure physical parameters. In conclusion, a further great research effort would be needed to clarify this controversial and important topic.
Keywords: Testis